Designing an optical frequency comb generator for visible light communication applications - Marwa Jaleel Mohsin; Ibrahim A. Murdas (Institute of Advanced Engineering and Science, 2022)
The optical frequency comb generator (OFCG) is an efficient optoelectronic device that is included in many important applications over a various field such as microwave and optical communication. A novel scheme of OFCG presented in this work for visible light communication application based on amplitude modulation, radio frequency (RF) signal, phase shift and two Mach-Zehnder modulators (MZMs), our design features are simple with more efficient power and premium flatness of comb lines, the number of generating frequencies lines was 64 with a power stronger than -2 dBm over a 340 GHz bandwidth from a single continuous laser diode. Different chirping factor (α) of MZMs are implemented (3, 5, 7), as the results the best results related to α=5 with extra flatness, the system was designed and simulated by VPI design suite 9.8.